2022
DOI: 10.3389/fnagi.2022.864662
|View full text |Cite
|
Sign up to set email alerts
|

Different Cortex Activation and Functional Connectivity in Executive Function Between Young and Elder People During Stroop Test: An fNIRS Study

Abstract: ObjectiveThe objective of this study was to examine the activation and functional connectivity of the prefrontal and temporal lobe in young and elder people during the Stroop test using functional near-infrared spectroscopy (fNIRS).MethodsA total of 33 healthy volunteers (20 young people, mean age: 23.7 ± 3.9 years; 13 elder people, mean age: 63.9 ± 4.0 years) participated in the study. All subjects were asked to finish the Stroop Color Word Test. The oxygenated hemoglobin concentration (Delta [HbO2]) signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…a higher WAB aphasia quotient). These findings suggest that right dorsal stream contributions to post-stroke speech could possibly be beneficial, but not by replacing the functionality of the left dorsal stream, but rather supporting the remaining left dorsal stream via more domaingeneral cognitive resources that have been previously located to right lateral frontal cortex (Reuter et al, 2011;Huang et al, 2022), and have been shown to be activated by a variety of speech and language tasks, particularly as task demands increase (Van Ettinger-Veenstra et al, 2010;.…”
Section: Functional Connectivity Patterns In Stroke Survivorsmentioning
confidence: 90%
“…a higher WAB aphasia quotient). These findings suggest that right dorsal stream contributions to post-stroke speech could possibly be beneficial, but not by replacing the functionality of the left dorsal stream, but rather supporting the remaining left dorsal stream via more domaingeneral cognitive resources that have been previously located to right lateral frontal cortex (Reuter et al, 2011;Huang et al, 2022), and have been shown to be activated by a variety of speech and language tasks, particularly as task demands increase (Van Ettinger-Veenstra et al, 2010;.…”
Section: Functional Connectivity Patterns In Stroke Survivorsmentioning
confidence: 90%
“…Since the cerebral blood oxygen signal collected by the NIR experimental equipment is in the time domain, converting the time domain signal to the frequency domain signal is the best way to gain insight into the relationship between blood oxygen changes in the prefrontal area and the degree of motion sickness [ 33 , 34 ]. In this study, the single channel basis with the most significant correlation features screened by PCA in the previous section was selected, and wavelet decomposition was performed on this channel.…”
Section: Methodsmentioning
confidence: 99%
“…[ 20 ] Only a few recent studies examined functional networks in the brain cortex using functional near‐infrared spectroscopy (fNIRS) and reported age‐related differences in brain activation [ 21 ] and measures of FC. [ 21 , 22 ] Contradicting the notion of impaired NVC, increased brain activity was observed in older adults [ 22 , 23 ] in response to cognitive stimulation which is associated with disrupted functional connectivity. [ 22b,c ] In contrast, other studies confirmed a generalized increase in FC, [ 24 ] but such changes are also regarded as reorganization of brain networks.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 , 22 ] Contradicting the notion of impaired NVC, increased brain activity was observed in older adults [ 22 , 23 ] in response to cognitive stimulation which is associated with disrupted functional connectivity. [ 22b,c ] In contrast, other studies confirmed a generalized increase in FC, [ 24 ] but such changes are also regarded as reorganization of brain networks. [ 22 , 25 ] Further research is needed in this emerging field to understand better the relationship between aging, cognitive performance, NVC, and FC in the brain cortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation